Preparation and characterization of GDC-Li2SO4/Li2CO3 nanocomposite electrolytes for applications in intermediate solid oxide fuel cells. Issue 15 (15th October 2017) - Li, Rongjie; Li, Chuanming; Cao, Liangliang; Zeng, Yanwei; Wang, Zhentao; Ye, Zhupeng; Zhang, Yuan
Abstract: Gd0.1 Ce0.9 O1.95 /Li2 CO3 -Li2 SO4 (GDC/LCS) nanocomposite electrolytes were prepared through nano-powders mixing, prefiring and sintering operations. The phase components and microstructures of the as-prepared nanocomposite were characterized by XRD, FESEM, TG-DSC and IR spectroscopy. AC impedance spectroscopy and DC polarization method were utilized to measure their electrical conductivities under different conditions. It has been found that the GDC/LCS nanocomposite have a very homogeneous microstructure, where the LCS is mostly in amorphous state due to the strong interfacial interactions between the GDC and LCS. In addition, their overall electrical conductivity was found to increase with temperature in air, featured with a sharp activation energy change from 1.01 to 0.30 eV around 520 °C, and reach 108.7 mS/cm at 600 °C, while their protonic and oxide ionic conductivities were 16 mS/cm in H2 and 5 mS/cm in air at the same temperature, respectively. The single cell built up of the GDC/LCS nanocomposite showed an open-circuit voltage of 1.01 V and peak power density of 272 mW/cm 2 at 600 °C.